Dialogue-enabling questions in academic writing tutorials - Wingate, Ursula; Ogiermann, Eva (Journal of Academic Language and Learning, 2022)
One-to-one academic writing tutorials are now being offered at many universities. They are seen as facilitative for student learning when conducted in a dialogic style. Questions have been shown to play a crucial role in dialogic teaching, and the type of questions asked by the teacher determines the student’s opportunity to make substantive contributions to the dialogue. Tutor handbooks tend to recommend the use of open-ended questions and discourage yes/no (polar) questions. The research presented in this paper examined the frequency, functions and types of tutor questions in ten tutorials involving six tutors and eight students. The objectives were to evaluate the advice on questions in tutor handbooks and offer evidence-based information for tutor training. The tutorials were ranked according to the frequency of topic-related questions. The results show that in half of the tutorials, fewer than 20% of the questions were concerned with the student’s topic or task, and that in some, very few questions were asked, indicating a monologic teaching style. In the more dialogic tutorials, it was apparent that, contrary to the advice in tutor handbooks, the majority of questions were polar and that this type of question was more successful in leading to substantive student responses than open-ended questions. Whilst questions in dialogic teaching have been widely investigated in classroom settings, this study is the first to examine dialogue-enabling questions in the rather different context of one-to-one academic writing tutorials.